TRANSFORMASI BUDAYA PESANTREN PASCA MEA - Rojak, Jeje Abdul (JURNAL MEDIA PENDIDIKAN AGAMA ISLAM, 2018)
After the implementation of the ASEAN Economic Community (MEA) at the end of December 2015, not many pesantren are ready to face it. There are those who survive to continue all the traditions (culture) inherited from generation to generation, without any change, innovation and improvisation. But there are also pesantren who try to transform based on the needs of the times. The case of Pondok Pesantren Darul 'Ulum, Rejoso, Peterongan, Jombang, East Java is one of the pesantren that at the beginning of the MEA has started the step of change by preparing human resources santri who go global / go ASEAN without leaving a religious feature thick with pesantren. This research seeks to reveal the transformation of pesantren culture in Pondok Pesantren Darul Ulum, Rejoso, Peterongan, Jombang and the extent of its impact on human resource competition after the implementation of MEA. Uses qualitative method with case study approach which gives detailed description about the background and nature of an event to describe the case by understanding the meaning and phenomenon. The results show that Pesantren Darul 'Ulum has been very adequate as an Islamic Education Institution preparing for the competitive generation in facing the challenge of free market in ASEAN region